Valorization of raw materials from agricultural industry for astaxanthin and β-carotene production by Xanthophyllomyces dendrorhous. Issue 13 (3rd July 2018) - Gervasi, Teresa; Pellizzeri, Vito; Benameur, Qada; Gervasi, Claudio; Santini, Antonello; Cicero, Nicola; Dugo, Giacomo
Abstract: Waste deriving from food and agro-industries is a growing problem in our modern society. In order to reduce food waste and its associated impacts over the environment and public health, innovative strategies for the conversion of food wastes in added value products are studied. Whey is one of the prominent waste deriving from Sicilian diary industry. The growth and the carotenoid biosynthesis of the yeast Xanthophyllomyces dendrorhous by its cultivation in pre-treated whey were studied. The study showed the possibility of increasing the astaxanthin productivity from X. dendrorhous in a batch fermentative process under continuous illumination. Our work is focused on the importance of carotenogenesis by X. dendrorhous on whey for the economic and ecological aspect. The results obtained in the study provide useful information about the possible use of this waste material for carotenogenesis from X. dendrorhous . Abstract :